The Impact of Educational Podcasts on Enhancing English Students’ Comprehensive Language Skills - Luma Adnan Taha, Luma Adnan Taha (مجلة الباحث, 2025)
The aim of this research is to examine the effectiveness of podcasts in enhancing students' listening comprehension in an EFL (English as a Foreign Language) classroom. 60 Iraqi high school students were selected for the study using cluster random sampling, and they were equally divided into an experimental group (30 students) and a control group (30 students). The study employed a quasi-experimental design, specifically the post-test only control group model. A survey questionnaire was also distributed to the experimental group to learn more about their opinions on podcast-based instruction. According to the findings, the experimental group's post-test scores were statistically significantly higher than those of the other group. With a significance value of 0.010, below the 0.05 cutoff, a one-way ANOVA analysis indicated that podcasts had a significant impact on students' listening comprehension. Furthermore, the survey's findings indicated that students' perceptions of podcast usage were positive. They asserted that by giving them engaging activities, accurate information, and worthwhile assignments, podcasts boosted their motivation to learn English. In light of these findings, the study recommends using podcasts as a technology-enhanced learning tool to teach listening in EFL classes.